2010
DOI: 10.1007/s13239-010-0005-7
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable Stents: Biomechanical Modeling Challenges and Opportunities

Abstract: Biodegradable implants show great potential in many areas of medicine, and have already demonstrated success in simple applications such as sutures. For more complex devices, such as vascular stents, there are considerable challenges associated with the use of biodegradable materials. These materials typically are weaker than the metals currently used to construct stents, so it is difficult to ensure sufficient strength to prop open the artery and alleviate symptoms acutely. It is even more challenging to desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 85 publications
(94 reference statements)
0
18
0
1
Order By: Relevance
“…There is not a model available yet to model the degradation process as well as property changes, especially to predict both biodegradable implant mechanics and its interaction with blood vessel. For instance, finite-element models were used to predict the recoil and collapse behaviour of polymer stent design by considering the elastic and/or inelastic behaviour of the polymer [46,47] , but neglecting any changes of material properties that occur [41] with degradation [48] . At human-body temperature, the biodegradation process is a combined effect of time and local deformation.…”
Section: Degradation Time (Days)mentioning
confidence: 99%
See 1 more Smart Citation
“…There is not a model available yet to model the degradation process as well as property changes, especially to predict both biodegradable implant mechanics and its interaction with blood vessel. For instance, finite-element models were used to predict the recoil and collapse behaviour of polymer stent design by considering the elastic and/or inelastic behaviour of the polymer [46,47] , but neglecting any changes of material properties that occur [41] with degradation [48] . At human-body temperature, the biodegradation process is a combined effect of time and local deformation.…”
Section: Degradation Time (Days)mentioning
confidence: 99%
“…The worldwide coronary stent market is worth over $7 billion and forecasted to grow by more than 5% annually [1] . Over the past three decades, there have been significant improvements made in stent materials and designs, especially for the drug-eluting stents (DESs) which were firstly approved by Food and Drug Administration (FDA) of USA in 2002.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies [22,23] have suggested bioresorbable stents, commonly referred to as scaffolds, as a possible future option for coronary intervention. As a consequence, polylactic acid (PLA) was chosen as the material during the design process.…”
Section: Med-15-1278mentioning
confidence: 99%
“…41 We assume d 5 0 for a virgin material while d 5 1 for a completely degraded material. These reaction equations would take place along the degradation and updated in the energy minimization procedure.…”
Section: Simulating Clip Degradationmentioning
confidence: 99%